Potensi Kawasan Wisata Desa Bahu Palawa Kabupaten Pulang Pisau: The Potential of the Tourist Area of Bahu Palawa Village in Pulang Pisau Regency - Jayadikarta, Ahmad; Aquarini, Aquarini; Toun, Nicodemus R.; Nurhasanah, Nurhasanah; Hamidah, Noor (HUTAN TROPIKA, 2024)
Bahu Palawa Village is one of the tourist destination areas in Pulang Pisau Regency, Central Kalimantan Province. Bahu Palawa Village is a village with unique nature and culture. Natural wealth, including agriculture, plantations, fisheries, crafts and house architecture, is found in Bahu Palawa Village. The aim of this research is to identify natural and cultural tourism areas in Bahu Palawa Village, Pulang Pisau Regency. The potential of Bahu Palawa Village was obtained from information from the village head and community leaders as an inventory of the development of a tourist area in one of the villages in Central Kalimantan Province. The research method uses a qualitative method with a descriptive approach through primary and secondary data collection. The research results show, among other things, identification of natural tourism potential, identification of cultural tourism potential, identification of artificial tourism, analysis of tourism development and analysis of tourism development policies in Kahayan Tengah District, Pulang Pisau Regency.